Components of the Glutathione Cycle as Markers of Biological Age: An Approach to Clinical Application in Aging - Estefania Diaz-Del Cerro; Irene Martinez de Toda; Judith Félix; Adriana Baca; Monica De la Fuente (MDPI AG, 2023)
The oxidative-inflammatory theory of aging states that aging is the result of the establishment of a chronic oxidative-inflammatory stress situation in which the immune system is implicated. Among the redox parameters, those involved in the glutathione cycle have been suggested as essential in aging. Thus, the first objective of this study was to determine if several components of the glutathione cycle (glutathione reductase (GR) and glutathione peroxidase (GPx) activities, and concentrations of oxidized glutathione (GSSG) and reduced glutathione (GSH)) in leukocytes) are associated with the biological age (ImmunolAge) estimated using the Immunity Clock in 190 men and women. The second objective was to identify the best blood fraction (whole blood, blood cells, erythrocytes, or plasma) to quantify these components and correlate them with the estimated ImmunolAge. The results show that the oxidative state of peripheral leukocytes correlates with their functionality, supporting the idea that this is the basis of immunosenescence. In blood, the correlations are more significant in the fraction of blood cells with respect to ImmunolAge (positive correlations with GSSG concentration and the GSSG/GSH ratio, and negative correlations with GPx and GR activities). Therefore, blood cells are proposed as the most effective sample to estimate the biological age of individuals in clinical settings.